Avaliação da ação antimicrobiana de diferentes irrigantes finais utilizando a contagem de unidades formadoras de colônias - Macci, Dierro Soares (2019)
The aim of this study was to evaluate, in vitro, the antimicrobial action of 17% EDTA and QMix against Enterococcus faecalis, by counting colony forming units (CFUs). Thirty extracted single-rooted human teeth were used for the present study. The coronal portion was sectioned with a diamond disk at the cementoenamel junction, so that the remaining root had a length of approximately 15 mm. Then, the samples were sterilized in an autoclave for 30 minutes at a temperature of 120°C. After the sterilization process, the samples were inoculated with 100 μl of Enterococcus faecalis culture and immersed in microtubes containing 2 ml of BHI. The samples were kept immersed in bacterial culture for fourteen days and stored in a bacteriological oven at a temperature of 37°C, with renewal of the culture medium every 48 hours, providing the necessary nutrients to sustain bacterial growth. After the contamination period, the samples were randomly divided into three groups (n=10) according to the final irrigation protocol: G1: distilled water; G2: EDTA 17%; G3: QMix. Counts of 4 colony forming units (CFUs) were performed to assess the decontamination effectiveness of the proposed treatments. Statistical analysis was performed using analysis of variance (ANOVA), followed by Tukey post-hoc (α=0.05). It was obtained as a statistical result that none of the groups completely eliminated the bacterial content, as well as that QMix was the irrigant that generated the greatest bacterial decontamination of the samples. It was then concluded that the antimicrobial action was greater when using QMix.